PEMBELAJARAN KOLABORATIF DAN KOOPERATIF KONSEP DASAR IMPLEMENTASINYA TERHADAP KEMATANGAN OBJEK DIDIK - FUAD (AZKIA : Jurnal Aktualisasi Pendidikan Islam, 2022)
Collaborative or cooperative learning does have a number of advantages, but this does not mean that it does not have limitations. aware that the success of collaborative or cooperative learning is highly dependent on a number of conditions. In collaborative learning, a conducive social environment is created for the implementation of interactions that combine all students' willingness and learning abilities. The environment is formed in the form of small groups consisting of four or five students in each class with group members that are not as homogeneous as possible. That is, the members of a group are attempted to consist of male and female students, students who are relatively active and less active, students who are relatively smart and those who are less intelligent. With such a composition, it is hoped that the role of tutors and tutees will be carried out between friends in each group